THE IMPACT OF HEDONIC SHOPPING MOTIVATIONS ON IMPULSIVE BUYING BEHAVIOR OF CONSUMERS IN APPAREL SECTOR IN GALLE DISTRICT - Selvarajan, P.; Chathuranga, R.W. L. (University of Jaffna, 2019)
The study attempts to examine the impact of hedonic shopping motivations on impulsive buying behavior of consumers. Based on the literature, Hedonic shopping motivations include the major six components called adventure shopping motivation, gratification shopping motivation, role shopping motivation, value shopping motivation, social shopping motivation and idea shopping motivation. The main objective of this study is to investigate the impact of hedonic shopping motivation on consumers’ impulsive buying behavior towards apparel sector in Galle district. The data were collected through a structured questionnaire from the respondents in Galle district. Researchers incorporated multiple linear regression analysis and reliability test by using the SPSS software of 20.0 version. The results showed that Adventure shopping, role shopping and idea shopping are significantly influencing on impulsive buying behavior. However, gratification shopping motivation, social shopping motivation and value shopping motivation showed an insignificant impact. Adventure shopping motivation and idea shopping motivation positively influence on impulsive buying behavior. Role shopping motivation is negatively influencing on impulsive buying behavior. It is concluded that the above stated six factors of hedonic shopping motivations have 70% impact on Impulsive Buying Behavior of consumers. It is recommended that the shopping store owners should display latest trendy cloths as much as possible to increase the hedonic shopping motivations of buyers.
Keywords: adventure shopping motivation; hedonic shopping motivations; impulsive buying behavior